The Effect Of Institutional Position, Role Ambiguity And Role Conflict On Internal Supervision Performance With The Independence Of Government Internal Supervisory Apparatus As An Intervening Variable - Raja Hafiz Hermawan; Chablullah Wibisono; Mohamad Gita Indrawan (Jurnal Ekonomi, 2024)
Supervision aims to assist all management in carrying out their responsibilities effectively by carrying out analysis, assessment, recommendations and submitting reports on the activities being audited. Based on the Summary of Semester Audit Results (IHPS) I of 2023, 5,628 SPI weakness problems were revealed, including 1,695 (30%) problems of weaknesses in the accounting and reporting control system, 2,974 (53%) problems of weaknesses in the budget implementation control system, and 959 (17%) problems of weaknesses in the internal control structure. A total of 7,227 non-compliance problems that have a financial impact include non-compliance problems that can result in losses of 3,520 problems amounting to IDR1.73 trillion, potential losses of 671 of IDR381.11 billion, and revenue shortfalls of 1,015 problems amounting to IDR960.11 billion. The above phenomenon indicates that the internal supervision function in the public sector is not yet effective. Internal Supervision Performance is very instrumental for the implementation of regional government. The Government Internal Supervisory Apparatus (APIP) does not have sufficient integrity and capability, the supervisory apparatus is not truly independent, and the need for the number of supervisory apparatus personnel has not been met. This study aims to test the influence of institutional position, role ambiguity and role conflict on Internal Supervisory Performance at the Regional Inspectorate throughout the Riau Islands Province by making the independence of the Government Internal Supervisory Apparatus as an intervening variable. The design of this study is quantitative research, using a mixed method, namely a questionnaire and supporting theories. The data analysis technique uses the Partial Least Square (PLS) approach to test the two hypotheses proposed in this study. Based on the results of the study, it was concluded that the Institutional Position variable has a significant positive effect on the Independence of the Government Internal Supervisory Apparatus (APIP), Internal escort performance at the Regional Inspectorate throughout the Riau Islands Province, while through the independence of Internal Supervisory Performance it has a positive but insignificant effect. The Role Ambiguity variable has a positive but insignificant effect on the APIP Independence variable, Internal Supervisory Performance. The Role Conflict variable has a positive but insignificant effect on the Internal Supervisory Performance variable. The APIP Independence variable has a significant positive effect on the Internal Supervisory Performance variable.